Development and validation of novel method for simultaneous estimation of Atovaquone and Mefloquine hydrochloride in bulk drug using RP-HPLC - Sharma, Sanyam; Ankalgi, Amar Deep; Sharma, Rahul; Devi, Arti; Jindal, Shammy; Goyal, Kamya (Creative Pharma Assent, 2020)
Atovaquone and Mefloquine hydrochloride are well known anti-malarial drugs. Literature survey reveals that there was no method available for the selected drug combination. In this way, here an endeavour has been made to develop simple, precise, fast method for simultaneous estimation of atovaquone and mefloquine hydrochloride in bulk drug by using RP-HPLC method. The method was carried out by using gradient HPLC on C18 column using Shimadzu prominence LC 20 AD and mobile phase comprised of Methanol:ACN:Water in the ratio of 85:7.5:7.5 (pH 2.9 was adjusted with OPA). The method was performed with 10µl injection volume. The UV detection was done at 231nm.The retention times of atovaquone and mefloquine hydrochloride were 7.6 and 2.6 min respectively. The proposed method was validated according to ICH guidelines. The validation parameters were linearity, accuracy, precision (inter-day, intra-day and repeatability) and robustness etc. Linearity was in the range of 80-120µg/ml for atovaquone and 40-60µg/ml for mefloquine hydrochloride. The percent recoveries of both drugs were 99.99-100% and 92.05-99.09%. This method is suitable for the routine analysis of atovaquone and mefloquine hydrochloride in bulk drugs either individually or in mixture